Antidiabetic Activity of Andrographis paniculata - Hossain, Md. Alamgir; Roy, BK; Ahmed, Kabir; Chowdhury, AM Sarwaruddin; Rashid, MA (Dhaka University Journal of Pharmaceutical Sciences, 2007)
The hot water and ethanol extracts of Andrographis paniculata (local name Kalomegh) collected from Chittagong exhibited a significant hypoglycemic (blood glucose lowering) activity in both glucose-loaded and alloxan-induced diabetic rats. Oral administration of glucose (1.5 g/kg body weight) increased the blood sugar level while the intraperitonial (ip) administration of alloxan (40 mg/kg body weight) enhanced the blood sugar level much higher than that of the glucose-loaded rats. The hot water (0.8 g/kg b.w.) and ethanol extracts (2 g/kg b.w.) of A. paniculata reduced the elevated glucose level by 41.51 and 41.82%, respectively in glucose-loaded rats as compared to the respective diabetic control rats. On the other hand, administration of hot water and ethanol extracts of A. paniculata decreased the blood sugar level by 46.21 and 45.13%, respectively in alloxan-induced diabetic rats, when compared with that of diabetic control rats. Keywords: Andrographis paniculata, Glucose-loaded, Alloxan-induced, Rats, Antidiabetic. Dhaka Univ. J. Pharm. Sci. 6(1): 15-20, 2007 (June) The full text is of this article is available at the Dhaka Univ. J. Pharm. Sci. website